Service quality, financial-spiritual benefits, and dual-pathway loyalty: Evidence from Indonesia’s largest Islamic bank - Farhan, Fikri; Wulandari, Azhari Putri; Zalzalah, Guruh Ghifar; Slamet, Slamet; Gustina, Adin (Asian Journal of Islamic Management (AJIM), 2025)
Purpose – This study examines how service quality and financial and spiritual benefits influence customer satisfaction and loyalty in Indonesian Islamic banking, with satisfaction acting as a mediating variable.Methodology – Data were collected from 300 customers of Bank Syariah Indonesia (BSI) in Java using a structured questionnaire. The relationships among variables were analyzed using partial least squares structural equation modeling (PLS-SEM).Findings – The results show that service quality, financial benefits, and spiritual benefits significantly enhance customer satisfaction. Service quality and financial benefits have direct effects on loyalty, whereas spiritual benefits primarily influence loyalty indirectly through satisfaction. Mediation tests revealed that satisfaction serves as both a complementary and an indirect mediator, depending on its antecedents.Implications – The findings highlight the importance of integrating functional and spiritual value propositions into loyalty-building strategies for Islamic banks. Enhancing service quality, offering competitive financial advantages, and ensuring consistent adherence to Islamic principles are essential to strengthening long-term customer relationships.Originality – This study extends the service quality–satisfaction–loyalty framework by incorporating financial and spiritual benefit dimensions, offering new empirical evidence on how Islamic values complement conventional satisfaction models within the emerging Islamic banking context of Indonesia.